KESANTUNAN TINDAK TUTUR MAHASISWA DALAM INTERAKSI PEMBELAJARAN DARING DI MASA COVID-19 - Kesya Nirma Lumbantobing; Nova Irwan (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
This research title is A Form of The Students Language Politeness in Online Learning Interaction in the Covid-19 period. This study aimed to describe and explain the propriety of speech act in online learning interaction in the Covid-19 period, as well as being a reference for lecturers, providing benefits for the STIKes Binalita Sudama Medan and society in general. This study includes the type of qualitative research using ethnography of communication design theory, speech act theory, and the theory of linguistic politeness. This study used a qualitative approach. This research was conducted for students of Refraksi Optisi STIKes Binalita Sudama Medan. Data collected through recording techniques, observation, interviews, and transcriptions. Data analysis was carried out through four main procedures, namely: data collection, data reduction, data presentation, and conclusion/verification. From this study, it was found several types of speech act politeness classifications used by students in learning interactions in Covid-19, namely: politeness in assertive acts, politeness in directive acts, politeness commissive acts, and politeness in expressive acts.